The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1108/13522751011032584
|View full text |Cite
|
Sign up to set email alerts
|

Wal‐Mart is coming to Guelph: hedonic to utilitarian shoppers' perceptions

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Interestingly, a qualitative study of Canadian Wall-Mart stores suggests that perceived shopping value is dependent on store location in towns or cities. In other words, the perceived hedonic value is greater for downtown shoppers, due to store atmospherics and the availability of products and services (Teed et al 2010). This assumption is aligned with the notion that consumers expect retailers to consistently deliver a minimum level of utilitarian value, and recognize the hedonic value of a shopping experience as an effective source of differentiation for stores as a brand (Carpenter, Moore, and Fairhurst 2005).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Interestingly, a qualitative study of Canadian Wall-Mart stores suggests that perceived shopping value is dependent on store location in towns or cities. In other words, the perceived hedonic value is greater for downtown shoppers, due to store atmospherics and the availability of products and services (Teed et al 2010). This assumption is aligned with the notion that consumers expect retailers to consistently deliver a minimum level of utilitarian value, and recognize the hedonic value of a shopping experience as an effective source of differentiation for stores as a brand (Carpenter, Moore, and Fairhurst 2005).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In fact, more research is needed on this aspect (Sherman et al, 1997). According to Teed et al, (2010), utilitarian values incorporate economic and functional values. They also suggested that lowering prices and one stop shopping accommodation are useful strategies for the retailers to meet these values.…”
Section: Customers' Shopping Motivationsmentioning
confidence: 99%